Peculiarities of translating national and cultural realities from Russian into Turkic languages - Rushongul , Mansurova (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
The article examines the peculiarities of translating national and cultural realities from Russian into Turkic languages. Special attention is paid to the ways in which culturally specific concepts, idiomatic expressions, and realia reflecting Russian traditions, lifestyle, and mentality are rendered in the context of Turkic linguistic systems. The research emphasizes the challenges of equivalence, adequacy, and preservation of semantic and stylistic nuances. Various strategies of translation such as transcription, calque, descriptive method, and functional substitution are analyzed. The study concludes that successful translation of national and cultural realities requires not only linguistic competence but also profound knowledge of the target culture to avoid semantic loss and misinterpretation.